Implantable Collamer Lens for Visual Rehabilitation in keratoconus - A Narrative Review of Visual and Refractive Outcomes - Rafah Fairaq; Halah Bin Helayel; Halla Abdulhadi; Sarah M. Almuwarraee; Sarah A. Almatrafi; Rahaf Alruwaili; Danya AlDahan; Sami T. Hameed; Mohammed AlShehri; Mohammed AlMutlak (JFO Open Ophthalmology)
Keratoconus (KC) is a progressive corneal condition characterized by ectasia, which causes progressive myopia and irregular astigmatism, resulting in decreased vision. Visual rehabilitation and refractive error management of keratoconic eyes are challenging. There is increasing interest in using the implantable collamer lens (ICL) off label in KC in light of encouraging reports of safety and efficacy in stable disease. The main concerns in considering ICL for visual rehabilitation include stability of the disease, magnitude of the refractive error, type of astigmatism, keratometric readings, and patient satisfaction with spectacles. This article reviews the indications for ICL in keratoconus and the timing between ICL implantation and corneal crosslinking and/or intrastromal corneal ring segment procedures. Additionally, we review challenges with ICL sizing in keratoconus, along with the factors and frequency associated with exchange and rotation post-ICL implantation.